Language code-mixing and its Language code-mixing and its underlying reason of use for a better teaching planning - Erlyna Abidasari; Ayu Lestari (Jurnal Pendidikan Profesi Guru, 2020)
Language mixing (code-mixing) is widely regarded as an obstacle to learning the Indonesian language. This research is intended to analyze code-mixing in understanding a target language. This qualitative study was carried out with the non-participant observation technique and semi-structured interviews for students at the beginner level of the Indonesian speaking class. Observations were done in five sessions for twelve students, while interviews were conducted for four students with the highest frequency of code-mixing. Information confirmation was also made to BIPA teachers to ensure data accuracy. The interview process was carried out immediately after observation to avoid losing too much information about code-mixing use. Data were analyzed using Muysken’s theory of bilingualism to classify code-mixing types. The results showed that there were 23 insertions, five changes, and one congruent lexicalization. Furthermore, 18 code-mixes were found in the form of words, five phrases, five clauses, and one abbreviation. The purposes of using code-mixing were to create an international atmosphere in the classroom, to replace vocabulary items that were not known in Indonesian, to achieve language familiarity, and to ensure understanding in the target language, as students might be able to get help when saying words or sentences in an international language, such as English